The Use of Figurative Language and Meaning in Halu and Runtuh Song Lyric - Andriani, Margareta (Journal of English Education and Teaching, 2024)
This article discusses and examines the use of figurative language and the meaning contained in the lyrics of the songs entitled 'Runtuh' and 'Usik' by Feby Putri. Feby Putri's songs are often considered a reflection of reality or facts, addressing problems commonly faced by teenagers and adults. Therefore, these things can be motivation and learning tools for the millennial generation to better understand and overcome the various challenges they face. The method used in this research is descriptive qualitative. Based on observations, the song 'Runtuh' by Feby contains 4 comparative figurative meanings, while the song 'Usik' uses 3 comparative figurative meanings and 1 example of metaphorical language. These songs are created poetically with meaningful symbolism. The song 'Runtuh' reminds us not to deceive ourselves and to remain honest with our feelings even though it is difficult. This describes the feelings of someone who always looks happy but actually has a hurt heart. On the other hand, the song 'Usik' conveys the message not to give up and continue to struggle to overcome challenges, to emerge as an individual who is stronger, more resilient, and believes in God's presence.